The Antecedents and Consequences of Customer Inspiration: The Mediating Role of Perceptual Fluency in the Online Shopping Context - Kasamani, Tamara; Abass, Alaa; Mostapha, Nehale (International Review of Management and Marketing, 2022)
Customer inspiration is gaining scholars attention in the marketing literature. Thus, the main objective of this study is to highlight on customer inspiration in the online shopping context, and this could be by examining the role of augmented reality (AR) in promoting customer inspiration. Minimal number of research have studied the effect of two critical dimensions of AR which are environmental embedding and simulated physical control on customer inspiration. Thus, this research will bridge this gap by conducting a quantitative study that empirically validates the effect of these two important variables on customer inspiration. Besides, this will open new insights for the future research to explore other variables and better understand AR. In addition, few studies have validated the theory of processing fluency in the AR context. Hence, this study will close the gap and investigate the role of perceptual fluency as a mediator to the relationship between AR and customer inspiration